Innovation and competitiveness of pharmaceutical companies in the European Union - Musil, Marek (2023)
The pharmaceutical industry is a strategic sector for the European Union from both an economical and public health perspective. We assessed that European firms are competitive within the international pharmaceutical market, but their position might be affected by the lower rates of innovation compared to companies from the United States and the continuous strengthening of Chinese pharmaceutical firms. Furthermore, we discussed how the drug development works within the industry, demonstrating that innovation demands considerable financial resources and highly qualified personnel. Lastly, we analysed the strategy of the European Union to improve the environment for the pharmaceutical firms with a special focus on the artificial intelligence and how it can revolutionize healthcare.